Utilization of Iron Ore Tailings as Raw Material for Portland Cement Clinker Production - Li Luo; Yimin Zhang; Shenxu Bao; Tiejun Chen (Advances in Materials Science and Engineering)
The cement industry has for some time been seeking alternative raw material for the Portland cement clinker production. The aim of this research was to investigate the possibility of utilizing iron ore tailings (IOT) to replace clay as alumina-silicate raw material for the production of Portland cement clinker. For this purpose, two kinds of clinkers were prepared: one was prepared by IOT; the other was prepared by clay as a reference. The reactivity and burnability of raw meal, mineralogical composition and physical properties of clinker, and hydration characteristic of cement were studied by burnability analysis, differential thermal analysis, X-ray diffraction, and hydration analysis. The results showed that the raw meal containing IOT had higher reactivity and burnability than the raw meal containing clay, and the use of IOT did not affect the formation of characteristic mineralogical phases of Portland cement clinker. Furthermore, the physical and mechanical performance of two cement clinkers were similar. In addition, the use of IOT was found to improve the grindability of clinker and lower the hydration heat of Portland cement. These findings suggest that IOT can replace the clay as alumina-silicate raw material for the preparation of Portland cement clinker.